(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2024)
The Mount Hamiding protected forest is located in North Halmahera district, North Maluku Province, Indonesia, which has high biodiversity but has not been managed optimally. In general, the study shows that communities around forest areas have low incomes. However, actual data regarding community welfare at the location level is unavailable. This research aims to assess the level of community welfare and income distribution in protected forest management. The methods used in this research are descriptive qualitative, quantitative. Data collection was carried out through observation, interviews, and literature study. Analysis of the level of community welfare refers to Sayogjo and inequality is measured using the Lorenz curve. The welfare level variable is determined using non-parametric chi-square statistical analysis. The research results show that people still live below the poverty line, and the average per capita income is IDR 3,913,255/year, the Gini Ratio is 0.3 in the low category. Community characteristics: education, number of dependents, distance from house to forest, income, and length of residence have a significant effect on welfare. Meanwhile, age, occupation, and land area do not have a significant effect. To improve community welfare, multi-party collaboration is needed for training and community empowerment activities.